Prostate-Specific Membrane Antigen Uptake in a Peripheral Nerve and Respective Ganglia on 68Ga–Prostate-Specific Membrane Antigen–HBED-CC PET/CT. (January 2021) - Mettler, Jasmin; Drzezga, Alexander; Dietlein, Markus; Hucho, Tim; Kobe, Carsten
Abstract : Abstract: A 74-year-old man with a history of prostate cancer with proven osseous metastatic disease underwent 68 Ga-prostate-specific membrane antigen (PSMA) PET/CT under antiandrogen therapy. The scan revealed a long segment of increased PSMA tracer uptake within the right sciatic nerve, which appeared edematous and swollen, and the respective ganglia. Clinically, the patient suffered from pain and paresis in the right leg. As infiltration of a long segment of a single nerve seems unlikely, primarily neuronal disease such as neuritis (induced by metastases or radiotherapy) was considered. The observed uptake of PSMA-targeting PET tracers may then represent a peripheral nerve disorder.